Sie sind auf Seite 1von 1
TOPIC :
FUNCTIONS
Absolute Valued Functions
Eg:
f (x) =
x − 2
Function Notations
1) Find the possible values of x
• f : x → x + 2
if f(x)
=
3
Solution
CONCEPTS MAP
(means the function f maps x onto ” x + 2
x - 2
= 3
,
x = 5
• f (x) = x + 2
’ f
of x is x + 2
-
(x - 2) = 3
,
x = -1
RELATIONS
• x is the object
,
f (x) is the image
2) Sketch the Graph of
Examples:
f (x) =
x − 2
for the
a)
If 5 is the object , find the image
Solution : f ( 5)
=
5 + 2 = 7,
domain
-1
x ≤ 6
How to represent
Relations
Solution:
Types Of Relations
b)
Given
f (3 y)
=
11 , find y.
x
= -1 ,
f(x) = 3
x
= 5
f(x) = 3
1. One-to-one relation
Solution:
f ( 3y)
=
3y + 2
= 11,
1) Arrow diagram
3 y = 9
y = 3
,
,
f(x) = x-3 = 0,
x = 3
2
3
f (x)
F
a•
•1
4
5
U
Composite Functions
3
6
7
b•
•2
N
x
c•
• If a function f is followed by a function g ,
we obtain the composite function g f .
•3
C
-1
0
3
6
2. One-to-many relation
3)
Co
rre
sp onding
T
g
d•
• f
Range:
•4
x
f (x)
g f (x)
0
≤ f(x) ≤ 3
1
4 I
2) Ordered Pairs
(a,1) (b,2), (c,2),
5 O
gf
3
Inverse functions (f -1 )
(d,3)
• In general gf ≠ fg .
6 N
• Concept:
f(x)
=
y
,
Then, f –1 (y)
= x
3) Graph
S
• How to determine composite function:
3
Eg:
3. Many-to-one relation
Example : Given
f : x x
+1
f –1
Given
f : x 2x + 1. Find
2
×
g : x
2x
Solution:
×
×
7
Determine
i.) f g
ii ) f 2
y −1
6
1
y
= 2x + 1
, x
=
s
Solutions;
×
9
10
2
i.)
fg (x)
=
f (g (x)
(ii) f 2 (x)
= f f (x)
x − 1
11
14
=
f
( 2x )
= f (x +1)
So ; f –1 (x)
=
a
b
c
d
2
=
2x
+ 1
= (x +1) +1
=
•Note: Only one – to – one functions will
x
+
2
Objects : a, b, c, d
Domain : {a, b, c, d}
Eg.• Given
f : x 2x
and
give one – to – one inverse functions.
4. Many-to-many relation
g f: x 3x - 1, find g.
ff -1 (x)
= f -1 f (x)
= x
Solution: g (f(x) = 3 x -1
1 5
Eg.• Given f : x 2x and
f g: x x + 3, find g.
Codomain : {1, 2, 3,4}
g( 2x)
= 3x
- 1
f(x) = 2x+1
− 1
x
− 1
Solution: f (g(x) ) = x + 3
f
(
x
) =
2
Lets 2x = y, x= 2 y
,
2 g(x)
= x
+ 3
Images : 1,2,3
2 7
ax
+ b
dx
+
b
x + 3
Range :
{ 1, 2, 3 }
f
(
x
) =
f
(
x
) =
3 x
g(x) =
cx
+ d
cx
a
g(y) = 3( 2 y ) -1,g(x) =
1
2
2